The Relationship of Servant Leadership on Knowledge Sharing Behavior With Organizational Culture and Organizational Citizenship Behavior As Mediator - Veronika Agustini Srimulyani; Sri Rustiyaningsih; Yustinus Budi Hermanto (Research and Development Agency Ministry of Home Affairs, 2023)
This study aims to analyze the relationship between servant leadership (SL) on organizational culture (OC), organizational citizenship behavior (OCB), and knowledge-sharing behavior (KSB) to test the indirect relationship of servant leadership (SL) on organizational culture (OC), organizational citizenship behavior (OCB), and knowledge sharing behavior (KSB), as well as to test the indirect relationship of SL to OCB and KSB through OC. The research design used a quantitative method; the research samples were 60 village officials from one of the sub-districts in Magetan Regency, East Java, Indonesia. Data collection was carried out by way of a survey using a questionnaire. The research results showed that SL has a significant positive relationship with OC and OCB, but SL does not have a direct relationship with KSB; OC has a significant positive relationship with OCB and KSB; OCB is not directly related to KSB; OC plays a partial mediating role in the relationship between SL and OCB; OC as a full mediation of the relationship between SL and KSB. Realizing KSB can be improved through the internalization of organizational culture, which can increase OCB and encourage organizational members to share knowledge.